A Versatile Toolbox for Multiplexed Protein Micropatterning by Laser Lithography. Issue 6 (19th November 2012) - Gropeanu, Mihaela; Bhagawati, Maniraj; Gropeanu, Radu A.; Rodríguez Muñiz, Gemma M.; Sundaram, Subramanian; Piehler, Jacob; del Campo, Aránzazu
Abstract Photocleavable oligohistidine peptides (POHP) allow in situ spatial organization of multiple His‐tagged proteins onto surfaces functionalized with tris(nitrilotriacetic acid) (tris‐NTA). Here, a second generation of POHPs is presented with improved photoresponse and site‐specific covalent coupling is introduced for generating stable protein assemblies. POHPs with different numbers of histidine residues and a photocleavable linker based on the 4, 5‐dimethoxy‐o‐nitrophenyl ethyl chromophore are prepared. These peptides show better photosensitivity than the previously used o‐nitrophenyl ethyl derivative. Efficient and stable caging of tris‐NTA‐functionalized surfaces by POHPs comprising 12 histidine residues is demonstrated by multiparameter solid‐phase detection techniques. Laser lithographic uncaging by photofragmentation of the POHPs is possible with substantially reduced photodamage as compared to previous approaches. Thus, in situ micropatterning of His‐tagged proteins under physiological conditions is demonstrated for the first time. In combination with a short peptide tag for a site‐specific enzymatic coupling reaction, covalent immobilization of multiple proteins into target micropatterns is possible under physiological conditions.